Study of Different Features and Classification Techniques for Recognition of Handwritten Devanagari Text - Vijay, Vijay; U Kharat, M; V Gumaste, S (International Journal of Engineering and Technology, 2018)
Devanagari script is most popular and an older script in India. Millions of people all over the globe are using Devanagri script for various purposes such as communication, understanding the history, record keeping, research, etc.Â  Recognition of handwritten Devanagari word is one of the popular area of research from decades because of its wide scope of applications. Different features and techniques of classification are the most important steps in the process of recognizing Devanagari handwritten word, are described in this paper.Â Â